2015
DOI: 10.1002/iub.1376
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of TMEM16a allostery in human retinal microarterioles in long‐standing hypertension

Abstract: We hypothesized that the calcium-activated chloride channel (CACC) transmembrane member 16A (TMEM16A) ionic mechanism may be a general mechanism in remodeling of vascular smooth muscles, including the retina. These vascular remodeling may have a critical impact on retinal ischemia during chronic hypertension. In this study, we examined TMEM16A protein interactions with calmodulin and CaMKIId likely cause efflux of chloride, thus resulting in increased vascular resistance by increasing vascular wall tone in lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…Recent inhibitors of TMEM16A, for example MONNA, CaCC(inh)‐A01 and T16A(inh)‐A01 , have been shown to suppress vascular constriction . However, our previous study demonstrated that these compounds relax rodent small mesenteric arteries even when the transmembrane Cl − gradient is abolished, suggesting a poor selectivity for TMEM16A .…”
mentioning
confidence: 74%
“…Recent inhibitors of TMEM16A, for example MONNA, CaCC(inh)‐A01 and T16A(inh)‐A01 , have been shown to suppress vascular constriction . However, our previous study demonstrated that these compounds relax rodent small mesenteric arteries even when the transmembrane Cl − gradient is abolished, suggesting a poor selectivity for TMEM16A .…”
mentioning
confidence: 74%
“…Calmodulin has been found to be required for Ca 2+ ‐dependent regulation of endogenous CaCC activity in many native cells such as olfactory sensory neurons (Kaneko et al, ), pulmonary artery endothelial cells (Nilius et al, ), airway epithelial cells (Wagner et al, ), and lymphocytes (Nishimoto et al, ). Recently, Gui et al () reported that TMEM16A directly interacted with calmodulin in retina blood vessels obtained from human patients with chronic hypertension. In the heterologous expression system, direct interaction between calmodulin and TMEM16A has been demonstrated by several studies using immunoprecipitation and pull‐down assay (Tian et al, ; Jung et al, ; Vocke et al, ).…”
Section: Structural Determinants Of Tmem16amentioning
confidence: 99%
“…35,83 However, hypertension-related downregulation of Ano1 has been always observed in the vasculature of the central nervous system, both in brain 63 and in the retina. 82 Thus, differences between previous reports may reflect modifications of Ano1 dynamics to adapt the vascular response to the specific needs of each tissue. Furthermore, studies in Ano1 knockout mice have demonstrated that the absence of this protein greatly reduces smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 91%
“…18,64 The fine analysis of arteriolar annuli in KAP transgenic mice demonstrated that VICs are altered during hypertensive retinopathy, because there was a marked decrease in Ano1 expression and NADPH diaphorase activity in these cells. Previous reports concerning the status of Ano1 during hypertension are discordant, with some studies arguing for reduced Ano1 expression 63 or altered allostery, 82 whereas other studies reported increased Ano1 activity. 35,83 However, hypertension-related downregulation of Ano1 has been always observed in the vasculature of the central nervous system, both in brain 63 and in the retina.…”
Section: Discussionmentioning
confidence: 94%